The tadpole of Dendropsophus novaisi (Bokermann, 1968) (Anura: Hylidae), with comments on natural history - Ruas, Danilo Silva; de Mira-Mendes, Caio Vinicius; Del-Grande, Maria Lúcia; Zina, Juliana; Solé, Mirco (Zootaxa, 2018)
Several frog species descriptions from this century provide larval morphology, acoustical, molecular, ecological and behavioral information that, together, provide a better species characterization (e.g., Glos et al. 2005; Toledo et al. 2010; Vassilieva et al. 2016). For the majority of anuran species, basic information is still lacking, despite being fundamental to understand the evolution of a taxonomic unit as well as phylogenetic relationships established between taxa. Such information can be particularly useful for species groups with unresolved taxonomic issues, such as the Dendropsophus marmoratus group (Bokermann 1964; Heyer 1977; Caramaschi & Jim 1983; Gomes & Peixoto 1996).